DRESS Syndrome due to Nevirapine Treated with Methylprednisolone - Henrique Pott Junior; Gisele Cristina Gosuen; Ana Cristina Gales (Case Reports in Medicine)
Nevirapine-induced DRESS syndrome is uncommon but a potentially life-threatening condition, with significant morbidity and mortality rates due to multiple-organ involvement. The authors report a case of a 47-year-old HIV-infected female patient who presented with fever, right hypochondrium pain, jaundice, and skin rash. The Nevirapine-induced DRESS syndrome was suspected based on clinical presentation and RegiSCAR scoring system. This case highlights the need for a high index of clinical suspicion among HIV-infected patients with severe skin eruption and systemic symptoms.